The Influence of Accounting Understanding and Internal Control Systems on the Quality of Financial Reports in MSMEs in North Maluku Province - Aspiati A. Samiun; Naswan Hadilia; Susmita Fataruba (JURNAL SAINS SOSIAL DAN HUMANIORA (JSSH), 2026)
This study aims to determine: (1) the effect of accounting understanding on the quality of financial reports, and (2) the effect of internal control systems on the quality of financial reports. The sampling method used purposive sampling. Data analysis used the Structural Equation Modeling–Partial Least Square (SEM-PLS) method. The results of the study indicate that accounting understanding has a positive and significant effect on the quality of financial reports, indicating that MSMEs with stronger accounting knowledge produce more reliable, transparent, and accurate financial information. Furthermore, internal control systems also significantly improve the quality of financial reports by reducing errors and minimizing the risk of fraud through proper monitoring and structured financial procedures. Together, these two variables significantly affect the quality of financial reports, indicating that accounting knowledge and effective internal control complement each other in improving accountability and supporting sustainable business decision-making processes.